Digital-Based Islamic Education Management And Its Role In Strengthening Students’ Literacy - Astri Riani Dewi; Yayah Rokayah; Try Riduwan Santoso; Jamaludin Jamaludin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study analyzes the representation of digital-based Islamic education management in strengthening elementary school students' academic literacy. The purpose of the research is to understand how optimizing education management to support digital literacy, integrating technology into Islamic religious learning, and strengthening academic literacy can enhance learning quality. This research method uses a qualitative descriptive approach. Data collection is carried out through observation, interviews, and documentation. The results show that digital literacy plays an important role in equipping students with the ability to filter information and develop critical thinking. Technology-based management of Islamic education can increase student participation. Students' academic literacy skills are significantly improved through the use of digital media and collaborative activities. This study emphasizes that implementing Islamic education management requires digital adaptation grounded in ethical and moral values. These findings are expected to be the basis for the development of a more effective technology-based PAI learning model.